CAUSES OF JUNIOR SCHOOL SCHOOL ANXIETY IN THE PROCESS OF LEADING ACTIVITY - O.I. Kostetska (Academy of Cognitive and Natural Sciences, 2010)
In article the reasons and mechanisms of occurrence of school uneasiness of the younger schoolboy in the course of educational activity are investigated.